ChemInform Abstract: CuFeS2 Quantum Dots and Highly Luminescent CuFeS2 Based Core/Shell Structures: Synthesis, Tunability, and Photophysics. Issue 49 (17th November 2016) - Bhattacharyya, Biswajit; Pandey, Anshu
Abstract: CuFeS2 quantum dots (QDs) are prepared by injecting both dodecanethiol and a sulfur solution in oleylamine into an equimolar FeCl2 and Cu(OAc)2 solution in octadecene and oleic acid at 180 °C.